PENGARUH PENGUNGKAPAN CSR ASPEK ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) TERHADAP RETURN ON ASSET (ROA) - Putra, Arifin; Megawati, Liya (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
Industrial development that increases and competes for profits results in a lot of environmental damage due to excessive resource exploitation. As a result, there is a lot of environmental damage and is detrimental to many parties, including the community. Therefore the government and other sectors issue regulations for industries to apply the principles of sustainability. In the principle of sustainability there is the concept of CSR which is the responsibility of the company in which there are aspects of ESG or Environmental, Social and Governance. This study aims to reveal whether the application of ESG aspects of CSR affects the profitability level of Return On Assets (ROA) in 7 companies listed on the ESG Star Listed Company Indonesia Stock Exchange 2017-2021. The analysis used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of testing the data obtained several conclusions as follows: (1) Partial test results for environmental aspects (Environmental) have no effect on Return On Assets, social aspects (Social) have no effect on Return On Assets, Aspects of governance (Governance) have a significant positive effect on Return On Assets. (2) The simultaneous test results of Environmental, Social and Governance aspects (Environmental, Social, and Governance) have a significant positive effect on Return On Assets (ROA).